Senior entrepreneurship and aging in modern business - Sáiz-Álvarez, José Manuel; Gámez Gutiérrez, Jorge Alberto (IGI Global, 2020)
""This book explores senior entrepreneurship from the perspectives of economics, sociology, international relations, and ethics"--Provided by publisher"--
Keywords: Older people / Employment; Businesspeople; Small business; Entrepreneurship